PERANCANGAN INTERIOR KEDAI KEBUN FORUM TIRTODIPURAN YOGYAKARTA - Indra Arista Ramadhan (Saraswati)
Yogyakarta is a city in Indonesia whose lively art and cultural activities attract local and international tourists. This uniqueness led Yustina Neni to build a restaurant, a gallery, and an art shop in one building. The number of art activities and artists’ interests to make exhibition in her space continuously increase, forces her to make a comfortable atmosphere there. The atmosphere is one of the most significant elements to build ideal exhibition circumstance in the gallery. The atmosphere is built through general elements in the space such as the floor, wall, plafond, furniture, and aesthetic elements.Based on the data collected through literatures, field studies, and survey done through the clients, staffs, and customers, the main problem occur is how to design the ideal interior to a restaurant, art shop and gallery. The interior design is not a mere general interior design, but is a specific set that can represent Kedai Kebun Forum’s character, meet the wants of the clients, and at the same time be a comfortable place for the customers and staffs.The management of Kedai Kebun Forum hopes that the gallery can be a comfortable space as a place for art appreciation in Indonesia. Besides, Kedai Kebun Forum hopes to be a café and restaurant that can represent Yogyakarta, not only Tirtodipuran area. They hope to make Kedai Kebun Forum as a cozy place to hang out in Yogyakarta, and at the same time is also chill, homey, and artsy. KEYWORD: Hangout-place, Art, homey